Signal and Image Analysis for Biomedical and Life Sciences - Sun, Changming; Bednarz, Tomasz; Pham, Tuan D.; Vallotton, Pascal; Wang, Dadong (Advances in Experimental Medicine and Biology, 2015)
Signal and image analysis techniques are becoming more widely used in biomedical and life science applications. With an emphasis on applications of computational models for solving modern challenging problems in biomedical and life sciences, this book aims to bring collections of articles from biologists, medical/biomedical and health science researchers together with computational scientists to focus on problems at the frontier of biomedical and life sciences. The goals of this book are to build interactions of scientists across several disciplines and to help industrial users apply advanced computational techniques for solving practical biomedical and life science problems. This book is for users in the fields of biomedical and life sciences who wish to keep abreast with the latest techniques in signal and image analysis. The book presents a detailed description to some of the applications. It can be used by those both at graduate and specialist levels.